Exploring energy transfer pathways for Tb³⁺ and Eu³⁺ through spectroscopic analysis of antenna-modified lanthanide-binding peptides - Al Mesfer, Mohammad, author; Kipper, Matthew, advisor; Snow, Christopher, committee member; Wilson, Jesse, committee member (Colorado State University. Libraries, 2025)
Lanthanide ions (Ln3+), such as Tb3+ and Eu3+, possess unique luminescent properties valuable for biological imaging. However, limitations including inefficient direct excitation and challenges in cellular delivery and sensitization hinder their application. Peptide-based complexes offer a promising platform for Ln3+ sensitization, providing biocompatibility and potential genetic encodability. This thesis investigates antenna-modified lanthanide-binding peptides (LBPs) designed to improve Ln3+ sensitization. A known LBP was engineered by replacing its native tryptophan sensitizer with cysteine, enabling site-specific conjugation of aromatic antennas (phenanthroline, pyrene, coumarin) via maleimide chemistry. This strategy aimed to optimize excitation wavelengths (shifting from ~280 nm). Successful bioconjugation was confirmed by MALDI-TOF MS. Spectroscopic analysis revealed distinct antenna-dependent effects on Ln3+ emission. Notably, the phenanthroline conjugate selectively sensitized Eu3+ (~615 nm) but not Tb3+ under identical conditions. Conversely, both pyrene and coumarin conjugates quenched Ln3+ luminescence. Attempts at cellular imaging following intracellular expression of the parent LBP were hindered by limitations in available microscopy instrumentation. Nevertheless, this research validates site-specific antenna conjugation as a strategy for modulating Ln3+ sensitization pathways. The findings provide insights into peptide-lanthanide energy transfer, inform the design of future LBP-based probes, and establish a foundation for subsequent development towards cellular applications.